Nutritional status of underfive children of Mumbai suburban region - Ghane, Vaishali R.; Kumar, Ranjith (International Journal of Research in Medical Sciences, 2017)
Background: Children below five years of age are an at-risk population due to their susceptibility to malnutrition. They contribute significantly for malnutrition related morbidity and mortality, especially in India. Malnutrition in under-five children belonging to middle or low-income group urban or suburban population is more severe and compounded compared to its rural counterparts. The objective of the study was to assess the nutritional status of under-five urban children. To study correlation of determinants like birth weight, exclusive breastfeeding, immunization status, maternal education and socioeconomic status with nutritional status of under five children. Methods: The prospective cross-sectional study included 315 under-five children attending paediatric outpatient department of upcoming new tertiary care hospital in Mumbai. Anthropometric assessment for underweight, wasting and stunting was calculated based on age, weight and height measurements. Results: As per WHO classification, moderate underweight (W/A) was present in 74 (23.49%) and severe underweight in 38 (18.71%). Wasting (W/H) in the form of moderate acute malnutrition (MAM) was noted in 64 (20.32%) and severe acute malnutrition (SAM) in 42 (13.33%). Height for age revealed moderate stunting in 37 (11.75%) and severe stunting in 5 (1.59%). The sociodemographic determinants birth weight, exclusive breastfeeding, immunization status, maternal education and socioeconomic status had statistically significant association with malnutrition. Conclusions: Malnutrition is common between age of 12 to 24 months. Underweight was the commonest type of malnutrition followed by wasting and stunting. None of the patient was overweight. Quality antenatal care to reduce incidence of low birth weight, exclusive breast feeding, and appropriate weaning, complete, immunization, improvement in maternal education and socioeconomic status can reduce the incidence of malnutrition.